The Tenth Marcel Grossmann Meeting, Part B on recent developments in theoretical and experimental general relativity, gravitation and relativistic field theories : proceedings of the MG10 meeting held at Brazilian Center for Research in Physics (CBPF), Rio de Janeiro, Brazil, 20-26 July 2003 (World Scientific Pub. Co., 2005)
The Marcel Grossmann meetings were conceived to promote theoretical understanding in the fields of physics, mathematics, astronomy and astrophysics and to direct future technological, observational, and experimental efforts. They review recent developments in gravitation and general relativity, with major emphasis on mathematical foundations and physical predictions. Their main objective is to bring together scientists from diverse backgrounds and their range of topics is broad, from more abstract classical theory and quantum gravity and strings to more concrete relativistic astrophysics observations and modeling. This Tenth Marcel Grossmann Meeting was organized by an international committee composed of D. Blair, Y. Choquet-Bruhat, D. Christodoulou, T. Damour, J. Ehlers, F. Everitt, Fang Li Zhi, S. Hawking, Y. Ne'eman, R. Ruffini (chair), H. Sato, R. Sunyaev, and S. Weinberg and backed by an international coordinating committee of about 135 members from scientific institutions representing 54 countries. The scientific program included 29 morning plenary talks during 6 days, and 57 parallel sessions over five afternoons, during which roughly 500 papers were presented. These three volumes of the proceedings of MG10 give a broad view of all aspects of gravitation, from mathematical issues to recent observations and experiments